PKM Tumbuh Kembang Balita Di Posyandu Smile Baby 3 Kelurahan Ujung Kota Surabaya - Anissa, Sabila Nur; Elvandari, Millyantri (Universitas Pahlawan Tuanku Tambusai, 2024)
The growth and development of a child does not solely depend on economic conditions of the family, but depends very much on the mindset of parents and the pattern of parenting given to children. The purpose of this community service program is to increase participants' understanding of the normal development of children aged 3 to 5 years, while providing knowledge about the importance of providing appropriate stimulation for their growth and development. This method of implementation will be conveyed through interaction in discussions, question and answer sessions, and weight assessments for children under five. The service was carried out at Smile Baby 3 Posyandu in Ujung targeting mothers who have toddlers, carried out on April 19, 2024. After completing the counseling activity, participants capable of understanding how to integrate toddler's development and match it with its ideal weight .